2019
DOI: 10.1002/jsfa.9440
|View full text |Cite
|
Sign up to set email alerts
|

Rice malting optimization for the production of top‐fermented gluten‐free beer

Abstract: BACKGROUND A safe method to obtain gluten‐free beer led to the use of naturally gluten‐free grains, such as rice, but the specific malting program for rice is long and requires a large amount of water, and the resulting beer showed a flat flavour profile. In this study, an optimization of the malting and brewing procedure is proposed to overcome the aforementioned issues. Different steeping conditions and kilning temperatures are considered, and a top‐fermented beverage from rice malt is obtained for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 26 publications
7
29
0
Order By: Relevance
“…For instance, rice malt for brewing tested on a pilot scale showed that the lautering process can be conducted normally using rice but with some color issues (Ceccaroni, Marconi, Sileoni, Wray, & Perretti, ). Beta, Rooney, and Waniska () investigated the malting properties of different sorghum cultivars obtaining similar characteristics to the commercial barley malts, suggesting that different cultivars can produce different malt qualities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, rice malt for brewing tested on a pilot scale showed that the lautering process can be conducted normally using rice but with some color issues (Ceccaroni, Marconi, Sileoni, Wray, & Perretti, ). Beta, Rooney, and Waniska () investigated the malting properties of different sorghum cultivars obtaining similar characteristics to the commercial barley malts, suggesting that different cultivars can produce different malt qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a staple food for nearly 50% of the world's population. According to the Food and Agriculture Organization [96]. Rice does not contain gluten-like proteins, so it is particularly suitable for consumption by individuals with celiac disease.…”
Section: Ricementioning
confidence: 99%
“…In the contemporary beer brewing industry, rice is primarily used as an adjunct in combination with barley malt. As a brewing adjunct, rice has a very neutral flavour and aroma, and when properly converted in the brew-house yields a light, clean-tasting beer [96]. Sensory analysis conducted on rice beers shows a pale yellow colour and a white coarse foam which rapidly collapses.…”
Section: Ricementioning
confidence: 99%
See 2 more Smart Citations